(untitled) (International Journal of Current Engineering and Technology, 2014)
In this paper, a new configuration of a UPQC called themulticonverter unified power-quality conditioner (MC-UPQC)is presented. The system is extended by adding a series-VSC in an adjacent feeder. The proposed topology can be used for simultaneous compensation of voltage and current imperfections in both feeders by sharing power compensation capabilities between two adjacent feeders which are not connected. The system is also capable of compensating for interruptions without the need for a battery storage system and consequently without storage capacity limitations.